Wujud dan Unsur Kebudayaan Upacara Penurun Hujan dalam Naskah Drama Ujungan Karya Widiyono - Setiyani, Annisa Indah; Israhayu, Eko Sri (Suara Bahasa, 2023)
Indonesia has many different languages, ethnicities and cultures based on their respective characteristics in each region. The characteristics of each in each area are used as an identity among the many ethnic groups in Indonesia. It is this diversity that makes Indonesia adhere to the motto Bhineka Tunggal Ika. It is the existence of these guidelines that makes the many cultures in Indonesia become one culture which is called Indonesian Culture. Culture is a characteristic that exists in every region that already exists or has been passed down from previous generations and passed on to the next generation. This is what is contained in the forms and elements of culture in drama scripts which contain the author's way of expressing events or a problem through character dialogues. The research conducted this activity aims to describe and analyze the forms and elements of culture in Widiyono's drama Ujungan. This type of research is included in the descriptive qualitative approach to literary anthropology. The data in this study are in the form of whole sentences or excerpts from the dialogues of the cast of the drama script which explain the forms and elements of Banjarnegara culture in the drama script entitled Ujungan by Widiyono. In data collection techniques using reading techniques, note-taking techniques and interviews. Data analysis used two steps, namely how to read the drama script, noting parts of the form and elements of culture, and conducting interviews with art activists in the Banjarnegara area to support research on the truth and authenticity of Banjarnegara art in Widiyono's Ujungan drama script. The results of the study reveal that the form of culture is divided into three, namely as a complex of ideas, ideas, values, norms, regulations, and so on; as a complex pattern of activities and actions of humans in society; and as human-made objects. In addition, the elements of culture are divided into seven, namely the language system, knowledge system, community organization system, living equipment and technology system, livelihood system, religion system, and arts system.Keywords: drama script, dialogue, cultural form, cultural elements, literary anthropology